STRATEGI PENGEMBANGAN DAN PEMASARAN KUBIS (BRASSICA OLERACEAE) (STUDI KASUS: NAGORI PURBATUA BARU, KECAMATAN SILIMAKUTA, KABUPATEN SIMALUNGUN, PROVINSI SUMATERA UTARA) - Mei Linda Sipayung; Jinni Ropi Girsang (Jurnal Darma Agung, 2019)
This study aimed at determining: (1) the cabbage farming development strategy in Nagori Purbatua Baru, Silimakuta District, Simalungun Regency, (2) the cabbage marketing channel in Nagori Purbatua Baru, Silimakuta District, Simalungun Regency and (3) the efficiency of cabbage marketing in Nagori Purbatua Baru, Silimakuta District, Simalungun Regency. The study was conducted in Nagori Purbatua Baru, Silimakuta District, Simalungun Regency, North Sumatra Province. The location selection was done purposively with the consideration that the location was one of the centers of cabbage vegetable production in Simalungun Regency. The sample was a portion or representative of the population being studied. The sample taking carried out by purposive technique or deliberately in determining the expert respondents consisting of 5 or more persons namely: cabbage farmers, collectors, large traders, students, government agencies and consumers. The analysis was done by using SWOT analysis and descriptive method. The results showed that the cabbage development and marketing strategy in the study area could be carried out with the W-O (Weakness-Opportunities) strategy, namely using high production to meet increasing market demand. Another alternative strategy that was also very well done was the S-T (Strength-Threats) Strategy, namely the use of regional conditions to increase production, was increasingly high. There are two cabbage trading channels in the study area, namely: channel (1), producer  collecting trader  retailer  end consumer and channel (2) producer  collecting trader à large trader  retailer  final consumer. There is no difference in the functions of each trading institution involved in cabbage trading in each channel in the study area. There were differences in trading margins (marketing margin, price spread, and large share margins of each cabbage trading agency in the study area. Share margins received by producers (farmers) were smaller than those of traders. Cabbage trading system efficiency levels in the study area were high , where channel I was more efficient than channel II.